Identifying Endometrial Delay Improves Treatment Outcome in Women with Thin Endometrium and Infertility (Central Asian Journal of Medical Sciences, 2024)
Objective: To determine the impact of endometrial delay on reproductive outcomes.Method: We enrolled 62 infertility women with thin endometrium pre- and post-study in 2020-2023. Infertile women with an endometrial thickness of